2022
DOI: 10.1177/13623613221140717
|View full text |Cite
|
Sign up to set email alerts
|

Realist evaluation of a transdisciplinary mealtime management service for autistic children

Abstract: Autistic children commonly experience mealtime difficulties; however, it is unknown what makes an effective transdisciplinary mealtime service for autistic children. This study used a realist evaluation framework to explore caregivers’ and therapists’ perceptions of the contexts, mechanisms and associated outcomes of a transdisciplinary mealtime management service for autistic children. Semi-structured interviews were conducted with six caregivers of autistic children engaged in a transdisciplinary mealtime se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…The caregiver's use of rehabilitation techniques in the normal daily life activity of the meal increases the number of eating sessions and promotes the generalization of learning. The results show that caregivers' presence in rehabilitation treatment is a key factor for successful treatment, in agreement with the current literature [46].…”
Section: Differences Between Gift and A Cognitive-behavioral Approachsupporting
confidence: 91%
See 2 more Smart Citations
“…The caregiver's use of rehabilitation techniques in the normal daily life activity of the meal increases the number of eating sessions and promotes the generalization of learning. The results show that caregivers' presence in rehabilitation treatment is a key factor for successful treatment, in agreement with the current literature [46].…”
Section: Differences Between Gift and A Cognitive-behavioral Approachsupporting
confidence: 91%
“…Chan and colleagues [46] revealed that most of the children with ASD who participated in their study had feeding disorders due to organic reasons, such as chewing disorders, choking, and oral motor and sensory disorders, which are all part of a speech-language pathologist's competence. There are various approaches to support feeding in children with ASD, which include systematic desensitization, escape extinction, and reinforcement.…”
Section: Differences Between Gift and A Cognitive-behavioral Approachmentioning
confidence: 99%
See 1 more Smart Citation